Video Interaktif Sebagai Media Interpretasi Gerak Tari Tradisional Siswa SMP - Raka Sukma Dewi; I Wayan Karja; I Gusti Putu Sudarta; Gede Pasek Putra Adnyana Yasa (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study aims to analyze the effectiveness of interactive videos in overcoming visibility constraints and students' psychological anxiety in traditional dance learning. Employing a descriptive-analytical qualitative approach, data were collected through observation, interviews, and Likert scale questionnaires from 30 8th-grade students and 1 teacher at SMP Nasional Denpasar. The results show that the slow motion and multi-angle features significantly reduce visual distortion, thereby increasing the accuracy of students' complex movement interpretations. Psychopedagogically, the use of personal devices successfully created a "safe space" that frees students from the pressure of social surveillance. This drastically reduced academic anxiety and encouraged students to practice freely and independently. Through the self-assessment mechanism, an 86.7% increase in student self-confidence was recorded. This interactive video also proved effective in distributing the teacher's instructional load. In conclusion, this media is highly effective as a pedagogical solution to facilitate learning autonomy and eliminate mental barriers during practice. Learning time becomes more efficient, providing educators with ample guidance space to focus on the transfer of aesthetic values and soulful expressions (wirasa).